EFEKTIVITAS METODE PEMBELAJARAN DARING TERHADAP MOTIVASI BELAJAR MAHASISWA SAAT PANDEMI COVID 19 DI KOTA PEKANBARU - Nia Desriva; Mona Dewi Utari; Arif Al Padri (Ensiklopedia of Journal, 2020)
Humanity is currently in deep sadness due to the outbreak of Coronavirus Disease (Covid-19) which has hit almost all parts of the world. Indonesia spontaneously implemented policies of learning from home, working from home, and worshiping at home. One of the learning methods used by the Indonesian education system is online or the abbreviation for the network. Online or online is a learning method that is carried out online. While online courses are courses that are wholly or partly held online or online, using learning management. Learning methods used in the learning process affect student motivation or interest in participating in the learning process. Modifying the learning process so that it attracts student attention will increase student motivation to learn even in the covid 19 pandemic conditions. This study used a pre-experimental design with a descriptive correlation design with a cross-sectional approach. The population in this study were all university students in Pekanbaru City. Sampling using the accidental sampling technique with 103 respondents and using t-test data analysis. Based on the influence test using the Paired sample T-test, it was found that the correlation of the Effect of Online Learning Methods on Student Learning Motivation had a significance of p = 0.000